Pengaruh Kampanye Politik Dan Media Sosial Terhadap Orientasi Politik Generasi Z Dalam Pemilu 2024 - Pamungkas, Oki; Damanhuri, Damanhuri (UNTIRTA CIVIC EDUCATION JOURNAL, 2024)
This study analyzes the impact of political campaigns and social media on Generation Z's political orientation in the 2024 General Election. The variables include political campaigns (X1), social media (X2), and political orientation (Y). Political campaigns are assessed through political rhetoric, agitation, and propaganda, while social media focuses on filter bubbles and echo chambers. Political orientation is measured across cognitive, affective, and evaluative dimensions. Using a quantitative, descriptive approach, the study finds that political campaigns positively influence all dimensions of political orientation. Political rhetoric enhances cognitive orientation, agitation affects affective orientation, and propaganda strengthens evaluative orientation. Social media also influences political orientation, with filter bubbles narrowing cognitive orientation by limiting diverse information and echo chambers reinforcing affective orientation by amplifying homogeneous views. The combination of political campaigns and social media significantly impacts political orientation. Social media accelerates campaign message dissemination but, through the interaction of filter bubbles and propaganda, may deepen political polarization and weaken critical evaluation. In conclusion, political campaigns and social media play pivotal roles in shaping Generation Z's political orientation.